Alpha power Weibull distribution: Properties and applications. Issue 20 (18th October 2017) - Nassar, M.; Alzaatreh, A.; Mead, M.; Abo-Kasem, O.
ABSTRACT: In this paper, a new lifetime distribution is defined and studied. We refer to the new distribution as alpha power Weibull distribution. The importance of the new distribution comes from its ability to model monotone and non monotone failure rate functions, which are quite common in reliability studies. Various properties of the proposed distribution are obtained including moments, quantiles, entropy, order statistics, mean residual life function, and stress-strength parameter. The maximum likelihood estimation method is used to estimate the parameters. Two real data sets are used to illustrate the importance of the proposed distribution.